Annual patterns of stratification, mixing and ventilation in long, deep, seasonally ice-covered François lake, British Columbia, Canada - Vagle, Svein; Carmack, Eddy (Frontiers in Earth Science, 2023)
François Lake is a long, deep, seasonally ice-covered, dimictic lake set in an east-west orientation in mid-British Columbia. As a baseline we here present data from a full-depth temperature mooring deployed at the lake’s mid-point in 2004-2005 and one full-depth CTD cast. We use these temperature records to define lake stability, scales of motion and the annual cycle of thermal stratification, mixing and deep-water ventilation. Owing to its length (110 km) both the Wedderburn and Lake numbers –indices of thermocline tilt and mixing under wind forcing - transition through critical values during fall and spring seasons, suggesting thermocline outcropping and strong turbulent mixing within the thermocline at these times. Owing to its depth (240 m) the temperature of maximum density (TMD) decreases with depth, adding complexity to overturn events. Owing to its seasonal ice cover (2-3 months per year) the critical periods for effective fall and spring ventilation lie between the dates that the lake surface water is below TMD yet absent of ice cover and wind shielding. While the lake undergoes full depth ventilation in both fall and spring, we show that that both progress in distinct dynamical stages, that fall ventilation is more efficient than that of spring, and that the transition temperature and resulting bottom temperature from fall to winter stratification (positive to inverse) and winter to spring stratification (inverse to positive) lies close to the temperature of maximum density calculated for the maximum depth of combined free and forced convection (in this case, closer to 3.7oC).